Reducing Divorce in Early Marriages: A Persuasive Communication Approach by Islamic Religious Counselors - Ahmad Fauzi Nasution; Dika Sahputra (Institut Agama Islam Negeri Kerinci, Indonesia, 2026)
This study investigates the role of Islamic Religious Counselors in mitigating divorce among early-marriage couples through persuasive communication. Although early marriage is frequently associated with an elevated risk of marital instability, limited research has explored how religious counseling contributes to divorce prevention. Employing a descriptive qualitative design, this study gathered data through observation and in-depth interviews with religious counselors and institutional leaders involved in marital guidance. Data were analyzed using Carl I. Hovland’s Persuasive Communication Theory. The findings indicate that Islamic Religious Counselors serve a critical function in preventing marital dissolution by deploying persuasive, dialogical, and non-judgmental communication. Key strategies include bidirectional communication, accessible language, storytelling, and family involvement. These approaches foster greater openness, emotional stability, and constructive conflict resolution among couples. Ultimately, this study underscores the potential of faith-based counseling as an effective communication strategy for strengthening marital resilience and reducing the risk of divorce in early marriages